2008
DOI: 10.1007/s10750-008-9545-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-term responses of decomposers to flow restoration in Fossil Creek, Arizona, USA

Abstract: Dam decommissioning projects, although numerous, rarely include complete sets of data before and after restoration for evaluating the ecological consequences of such projects. In this study, we used a before-after control-impact (BACI) design to assess changes in leaf litter decomposition and associated macroinvertebrate and fungal decomposers following dam decommissioning in Fossil Creek, Arizona, USA. Leaf litterbags were deployed in a relatively pristine site above the dam and a highly disturbed site below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Muehlbauer et al (2009) reported declines in macroinvertebrate diversity and fungal biomass on litter that were associated with slower breakdown rates under conditions of reduced flow, but retardation of breakdown related to flow reductions were only evident during the wet season, when stream flows were relatively high. The lack of any inter-reach difference during the dry season was similar to the findings obtained in inter-reach TTrich total taxon richness, exp H 0 diversity, Abun total macroinvertebrate abundance, Chir abundance of Chironominae, Shre shredder abundance, Brot abundance of Brotia hainanensis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Muehlbauer et al (2009) reported declines in macroinvertebrate diversity and fungal biomass on litter that were associated with slower breakdown rates under conditions of reduced flow, but retardation of breakdown related to flow reductions were only evident during the wet season, when stream flows were relatively high. The lack of any inter-reach difference during the dry season was similar to the findings obtained in inter-reach TTrich total taxon richness, exp H 0 diversity, Abun total macroinvertebrate abundance, Chir abundance of Chironominae, Shre shredder abundance, Brot abundance of Brotia hainanensis.…”
Section: Discussionmentioning
confidence: 98%
“…While stream flow alone plays a minor role in determining breakdown directly, its effect seems more usually indirect by way of an influence on biological processes (Woodcock & Huryn, 2005;Ferreira et al, 2006;Hoover et al, 2006). For instance, breakdown rates of two leaf species in an Arizona stream decreased by *20% when flows were reduced by 95%, and this decrease was associated with cooler temperatures as well as lower fungal biomass and macroinvertebrate diversity on the leaves (Muehlbauer et al, 2009). In other cases, flow reductions can accelerate litter breakdown as a result of increased nutrient loads that enhance fungal colonization (Short & Ward, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this, few studies have evaluated the effect of fluvial regulation on processes taking place in stream ecosystems, such as leaf litter decomposition (Short & Ward, 1980;Casas et al, 2000;Pomeroy et al, 2000;Muehlbauer et al, 2009;Mendoza-Lera et al, 2010). Dams can modify water temperature and chemical conditions such as nutrient concentrations, both of which may affect aquatic hyphomycete and macroinvertebrate communities, as well as the processing of organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the changes in flow regime, the upstream reach assemblage trait was not significantly modified. Casas et al, 2000;Muehlbauer et al, 2009), no physical impact on leaf litter breakdown rates was evidenced downstream the dams, in the absence of sediment contamination. In contrast, the dam impact was more pronounced in the downstream reference reach (Do1).…”
Section: Functional Disturbances Related To Dam Presencementioning
confidence: 94%